TINGKAT PEMAHAMAN MASYARAKAT TERHADAP HUTAN MANGROVE DI DESA PANGKALASEANG KECAMATAN BALANTAK UTARA KABUPATEN BANGGAI Moh Rifky L. Saad1 , Andi Sahri Alam2 , Budi Seti - L. Saad, Moh Rifky; Alam, Andi Sahri; Setiawan, Budi; Pribadi, Hendra (Jurnal Warta Rimba, 2021)
The mangrove forest is a unique and distinctive form of forest ecosystem, especially in the Indonesia area, because the mangrove forest is found in the ebb and flow of coastal, coastal, and small islands, and it is a potentially rich and competitive nature's resources. The mangrove forests have great economic and ecological value especially in coastal society, but they are particularly vulnerable to damage when the care of the society for the preservation and maintenance of the mangrove forest it self is reduced. The study was to find out the extent of the society understanding of the mangrove forest in the Pangkalaseang Village, North Balantak District, Banggai Regency. The study is carried out for 2 months, from June to August 2020. The method was used to identify the level of human understanding of the mangrove forest found in the Pangkalaseang Village, analysed using a descriptive method, with a scale of 1-3-5 (likert scale modification). The data-collection technique used in this research is observation, interview and documentation. The results of the study indicate that the level of understanding of the people in the pangkalaseang village is in high levels, indicating that the knowledge levels in the village of pangkalaseang are already familiar with the importance of the mangrove forest. The society understood that the presence of mangrove forests opened the way for society to manage so as to care for the life and economic needs of the families resulting from the manage of the mangrove forest.Keywords: Mangrove, Forest, Society